HIS bundle electrocardiogram in children with secundum atrial defects and patent ductus arteriosus - Bambang Madiyono; Hanafi B. Trisnohadi; Maemunah Affandi (Paediatrica Indonesiana, 1981)
The purpose of this swdy is to compare intra-atrial conduction (atrio-ventricular conduction and intraventricular conduction) in children with secundum atrial deptal defect (ASD II) and patent ductus arteriosus (PDA) using His bundle electrocardiogram (HBE).Six patienls with ASD II and seven with PDA, aged ranging from 3 to 11 years were included in the study. The diagnoses of all cases were confirmed by cardiac catheterization. The results of HBE studies showed that the PA, AH, HV, interval in ASD II were 31.7 ± 7.6 msec; 65.8 ± 16.8 msec; 42.5 ± 2.2 msec; and in eDA were 25 ± 7.8 msec; 77.9 ± 9.4 msec; 40 ± 3.8 I11sec respectively. The differences were statistically not significant (P > 0.05).The data showed that intra-atrial conduction in children with ASD II was not longer than that in PDA and also there was no difference in atrioventricular conduction and intraventricular conduction, although childrell with ASD II usually have abnormal ECG, like right bundle branch block.